Protection for Thorax Injury Severity in 90° Lateral Collision - Dimitrios Kallieris; Frank Boggasch; Rainer Mattern (Shock and Vibration)
The thoracic trauma index (TTI) and the viscous criterion (VC) are injury criteria intended for the prediction of torso injury severity. The criteria were assessed in two series of experiments: 90° (lateral) car to car collisions and controlled left trunk impacts against either a rigid or padded wall. Forty-two belt restrained human cadavers in the age range 18–65 years, located in the near-side front passenger seat, were used. The impact velocity was between 40 and 60 km/h. Left and right side impacts were simulated using standard or modified car side structures. With the second series of experiments, the left side of each subject was impacted under one of two different test conditions: 24 km/h rigid wall or 32 km/h padded wall. The thorax deformation was evaluated through the double integration of the accelerated difference at the fourth and eight ribs, near and far side. Deformation maxima of 6–138 mm (mean 69 mm), VC values of 0.3–4.7 m/s (mean 1.6 m/s), and TTI values of 85–252 (mean 63) occurred. Torso abbreviated injury severity (AIS) values were between 0 and 5. Statistical analyses showed a stronger influence of age on injury severity than the injury criteria or biomechanical responses in the two series of experiments. The TTI showed the highest correlation with thoracic AIS and the number of rib fractures, while VC was the better predictor of abdominal AIS. The results are discussed critically and the strength and robustness of the injury criteria analyzed.